What Really Matters in Secondary-Level Students’ Classroom Participation: A Study from the Student’s Perspective: A Study from the Student's Perspective (Teacher’s World: Journal of Education and Research, 2024)
Effectively Increasing student classroom participation has always been a crucial challenge for secondary teachers. The present study aims to address the factors that contribute to increased student participation in the classroom, therefore fostering an improved learning environment from the secondary-level students’ perspective. This study uses a qualitative research approach to explore specific aspects of teachers' behavior that impact student participation. Through focused group discussions, students share their diverse experiences and perspectives, the dimensions of teachers’ particular behavioral influence on active engagement in the classroom. The findings shed light on teachers’ content delivery skills, the role of teachers’ rapport building, the impact of teachers’ willingness to explain in depth, and the influence of teachers’ voices. The study suggests valuable insights for educators striving to create a more conducive and participatory learning atmosphere in secondary education. Teacher’s World: Journal of Education and Research, 49 (2),85-98